THE IMPACT OF CENTRAL BANK DIGITAL CURRENCIES ON BANK BALANCE SHEETS - Tursunova Ibodat Xo`jayor qizi (Journals Park Publishing, 2024)
This article reveals statistical and analytical data related to the impact of the issuance of CBDC on the balance sheet of the banking system and its liquidity and money circulation.
Keywords: Digital currency, CBDC, structural current surplus, structural liquidity deficit, correspondent accounts, liquidity provision and absorption operations, inflation, velocity of money, seigniorage, OMOs (open market operations).